Herbal Nano Formulations: Patent and Regulatory Overview - Dhawan, Surbhi; Hooda, Partibha; Nanda, Sanju (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2018)
Herbals have been explored worldwide from ancient times for their innumerable therapeutic applications. Despite the advantages, phytomedicines encounter several drawbacks like toxicity, lower bioavailability, stability problem and patient compliance. To overcome these constraints researchers came up with the introduction of Novel Drug Delivery Systems (NDDS). These included polymeric liposomes, nanolipid carriers, colloidosomes, solid lipid nanoparticles, aquasomes, niosomes, proliposomes, nanocapsules, ethosomes, phytosomes, nanoparticles, nanoemulsions, and transferosomes. Nanotechnology is being ventured as an emerging trend in the field of medicines eliciting improved therapeutic benefits. It reflects the interface between new technology and herboceuticals. These upcoming herbal formulations are being patented too. Since nanotechnology is slowly creeping into every aspect of life, a concern has been generated related to the human safety. Hence, the present time demands the regulations to be set up for nanomaterials. In this paper, an effort has been made to compile various herbal nanoformulations and patents and a glance on the regulatory aspects of various regulatory bodies on nanotechnology have been provided.
Keywords: regulatory bodies